Penerapan Model Pembelajaran BAMBOO DANCING untuk Meningkatkan Hasil Belajar Siswa Kelas V pada Materi Akidah Akhlak MI Nurussalam Ngawi - Nanang Setyobudi; Anisa Rohmatul Umah; Deyah Sapitri Sapitri; Eka Hidayatin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
Akidah Akhlak, a subject in Islamic religious education at MI Nurussalam, often presents challenges in student engagement due to its perceived monotony. In this study, the Bamboo Dancing learning model was implemented to address this issue, aiming to foster teamwork, concentration, communication among peers, and cognitive development. Students formed groups and moved in a clockwise manner while posing questions to their peers, enhancing their learning experience. The choice of the Bamboo Dancing learning model for the Akidah Akhlak subject was intentional, as it aimed to inject enthusiasm and interactivity into the learning process, which typically involves passive knowledge transfer from teacher to student. The study aimed to assess the effectiveness of this model in improving students' learning outcomes. Classroom Action Research (CAR) was employed as the research methodology. Results from the first cycle showed that 60% of students scored above 60, which increased to 80% in the second cycle. This indicates that the Bamboo Dancing learning model effectively enhances students' engagement and overall learning outcomes.